The Development of Edmitico: A Disaster Mitigation Comic as an English Vocabulary Learning Media for Students with Mild Intellectual Disabilities - Andi Arsyad; Indah Puspitasari; Samsul Hadi (Jurnal Langua, 2026)
Previous studies have generally focused only on English vocabulary learning or disaster mitigation education separately. There has yet to be an instructional medium that integrates both aspects in a single resource specifically developed for students with mild intellectual disabilities. The aim of this study is to develop a bilingual (Indonesian and English) disaster mitigation comic that combines English vocabulary learning with disaster mitigation education. This research used the Research and Development (R&D) method with the ADDIE model: analysis, design, development, implementation, and evaluation. The study was conducted on May 8–13, 2026, at SLB Negeri Ngadirojo, Pacitan Regency, involving three elementary students with mild intellectual disabilities. Media validation results showed a score of 90.5% from media experts (highly feasible) and 80.5% from material experts (feasible). Implementation showed an effectiveness rate of 87.5% (highly effective). The medium improved students’ attention, participation, and understanding of English vocabulary as well as earthquake and tsunami mitigation actions. Thus, the developed comic is considered feasible, practical, and effective as a learning medium for students with mild intellectual disabilities.